Suppression of charcoal rot in soybean by moderately halotolerant Pseudomonas aeruginosa GS‐33 under saline conditions. (23rd May 2016) - Patil, Sandeep; Paradeshi, Jayasinh; Chaudhari, Bhushan
Abstract : Charcoal rot severely limits the soybean crop yield under saline conditions. The present studies focus on biocontrol and plant growth promoting potential of phenazine producing moderately halotolerant Pseudomonas aeruginosa (GS‐33) in soybean under saline soil conditions. A marine isolate; GS‐33 was identified as P. aeruginosa based on polyphasic characterization. This strain showed potent in vitro biocontrol activity against charcoal rot causing fungus Macrophomina phaseolina . It was capable of producing phenazine‐1‐carboxylic acid even at elevated salt concentrations. Moreover, GS‐33 possessed other biocontrol traits like production of siderophores, HCN and protease under saline conditions. Multiple traits for plant growth promotion such as synthesis of IAA, NH3, and solubilization of phosphate were also exhibited by GS‐33. Plant growth promoting and biocontrol control potentials of GS‐33 were evaluated by pot assay under saline soil conditions. Higher biomass and chlorophyll content were observed in GS‐33 treated seedlings. A greater reduction in charcoal rot caused by fungal pathogens under both normal and saline soil conditions in GS‐33 treated seedlings was observed. In a nut shell, phenazine producing halotolerant strain GS‐33 could mitigate saline soil conditions (abiotic stress) and infestation of M. phaseolina (biotic stress) in soybean.